Sudden rupture of an acute retropharyngeal abscess in children: A grave lesson - Ibrahim, Mohd Irman Shah; Nik Mohd, Nik Khairani; Mohamad, Amran; Md Shukri, Norasnieda (Elsevier, 2016)
Retropharyngeal abscess (RPA) in children is becoming an uncommon entity in the era of antibiotics. Majority of the patients presented with neck swelling and fever while very few of them manifested any kind of airway compromise symptoms. Nevertheless, RPA can potentially be life threatening as the possible complications such as airway obstruction and sudden rupture of the abscess may occur if not treated promptly. There was no reported mortality in recent literatures. We reported an unfortunate boy who died from sudden rupture of the RPA.